Regional Usage in the English of Cape Breton Island - Falk, Lilian (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1990)
The present paper examines features of regional usage in the English of Cape Breton, Nova Scotia. Examples of syntactic constructions, grammatical forms, and vocabulary were extracted from one year's edition of Cape Breton's Magazine (1973). Non-Standard syntax includes especially certain types of extraposition of subject (e.g. my cousin, he made all kinds of knots) and asyndetic constructions. Grammatical forms and constructions include the formation of verb tenses (e.g. get, hear,, (I) says,, to refer to the past), plurals of nouns without formal markers, non-standard uses of prepositions (e.g.) into to indicate location, not direction) as well as pronouns, adverbs, and intensifiers. Comparisons with relevant regional word-books and dictionaries point out that most of these grammatical and syntactic features are shared with other parts of Atlantic Canada. Some items of vocabulary are also widely shared (e.g. dinner for midday meal) while others are shared with a specific region; thus for instance, eyestone is listed in the South Shore Phrase Book, killic in DPEIE and DNE. On the other hand such items as curiosity work or fyke nets point to links with older British usage.